Basaloid squamous cell carcinoma of oral cavity with incongruent clinical course. (19th September 2013) - Patel, Pratik Nalinbhai; Mutalik, Vimi Sunil; Rehani, Shweta; Radhakrishnan, Raghu
Abstract : Basaloid squamous cell carcinoma (BSCC) is a rare variant of SCC having a marked predilection for the upper aerodigestive tract. It is regarded as a high-grade tumour with increased propensity for metastasis to distant sites. The histological hallmark of BSCC is its dimorphic pattern of presentation with a characteristic basal cell component associated with squamous component. We report two cases of BSCC on the buccal mucosa and gingiva, respectively, with the former presenting as a primary lesion in a patient without a positive history of tobacco and alcohol use and the latter present as a seemingly metachronous development from carcinoma lung. The proliferative index of the two diverse yet similar entities was assessed by Ki-67 labelling index (LI) and the association of human papillomavirus (HPV) was detected with p16 monoclonal antibody. The intrinsically aggressive behaviour of BSCC and its association with HPV is highlighted.